2013
DOI: 10.1371/journal.pone.0070034
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde-Derived Advanced Glycation End-Products Promote Alcoholic Liver Disease

Abstract: BackgroundChronic ingestion of ethanol increases acetaldehyde and leads to the production of acetaldehyde-derived advanced glycation end-products (AA-AGE). We evaluated the toxicity of AA-AGE on hepatocytes and studied the role of AA-AGE in the pathogenesis of alcoholic liver disease (ALD).MethodsRat hepatocyte cultures were treated with N-ethyllysine (NEL) or AA-AGE and the cell viability was evaluated using MTT assay. Male Wistar rats were fed with liquid diet containing 5% ethanol for 8 weeks following norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 32 publications
(37 reference statements)
2
38
0
Order By: Relevance
“…Additionally, a study by Teichert et al showed that sAGE levels increased in the early stages of impaired glucose homeostasis. In the same context, chronic ethanol consumption induces metabolic changes, such as hyperlipidaemia and hyperglycaemia, and increases circulating AGEs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study by Teichert et al showed that sAGE levels increased in the early stages of impaired glucose homeostasis. In the same context, chronic ethanol consumption induces metabolic changes, such as hyperlipidaemia and hyperglycaemia, and increases circulating AGEs …”
Section: Discussionmentioning
confidence: 99%
“…Metabolic changes caused by chronic ethanol consumption, such as hyperlipidaemia, insulin resistance and increased circulating levels of advanced glycation end products (AGEs), contribute to renal dysfunction. Lipoproteins can mediate nephrotoxicity by inducing oxidative stress and pro‐inflammatory cytokine expression .…”
Section: Introductionmentioning
confidence: 99%
“…Data from this study demonstrated that AA-AGE is toxic to hepatocytes, but that N-ethyllysine was not. Additionally, chronic ingestion of ethanol produced oxidative stress, AA-AGE and 4HNE staining that all correlated with the degree of alcoholic liver disease in both rodent and human liver tissue (Hayashi et al, 2013).…”
Section: Acetaldehydementioning
confidence: 95%
“…Furthermore, chronic ingestion of ethanol increases acetaldehyde, a major toxic metabolic intermediate of alcohol detoxification that causes direct DNA damage, leads to the production of several end-products which contribute to the pathogenesis of ALD (Hayashi et al, 2013). …”
Section: Alcohol Liver Related Diseasementioning
confidence: 99%